Methodology for determining effect of starting modes of internal combustion engine on change in engine performance characteristics - N. A. Zagorodnii; Yu. A. Zayats; A. S. Semykina (Вестник СибАДИ)
Introduction. As part of solving the urgent problem of forecasting technical impacts and residual life depending on operating time, a method for determining the effect of the starting mode on a change in the structural parameter determining reliability is presented. The essence of this technique and its novelty consists in combining two full-factor experiments to determine the effect of operating conditions on changes in the structural parameters of the engine. The purpose of the scientific study is to determine the effect of the starting internal combustion engine on the change in the performance characteristics of the engine.The novelty of the article lies in the combination of two full-factor experiments to determine the effect of operating conditions on changes in the structural parameters of the engine that determine its reliability.The reliability of the car (individual reliability properties or technical readiness) is influenced by the following factors: operating modes, operating conditions, quality of spare parts, qualifications and experience of drivers, etc. These factors show the direction and degree of the influence on the car and its reliability (technical readiness). The paper examines the influence of each factor on the reliability of the car.Methods and materials. To determine the effect of the starting mode of an internal combustion engine on a change in the structural parameter during forecasting, it is necessary to develop a methodology for determining the effect of the starting modes of internal combustion engines on changes in the structural parameters of the engine that determine its reliability. This technique involves conducting a full-factor experiment with four factors, i.e. 16 experiments. The combinations of different levels of factors are accepted as operational modes.To measure the magnitude of the influence of each factor on reliability, the article considers their measured values - indicators of the factor. There are from one to several indicators per factor. The values of the indicators are not constant, but change in accordance with changes in external influences (factors). Indicators are calculated based on the values of certain indicators of the direction of the influencing environment that a particular indicator describes.The total duration of the tests is assumed to be equal to the resource before major repairs.Results. The authors propose a method for determining the effect of starting modes of internal combustion engines on changes in the structural parameters of the engine that determine its reliability.The starting modes of the internal combustion engine and the dependence of reliability properties on external factors affecting the car at the time of engine start are considered. It is established that the degree of influence of factors is measured by the values of their indicators.Conclusion. As a result of using the proposed methodology for determining the effect of starting modes of internal combustion engines on changes in the structural parameters of the engine that determine its reliability, the principal possibility of an integrated approach to determine the effect on the structural parameters that determine reliability in the course of one series of experiments of both the influence of operating modes and engine starts, as well as the possibility of determining the influence and extreme values of factors is shown for reliability.Thus, the calculation of the values of one or another indicator enables to obtain the final values of the components of reliability (technical readiness). Indicators enables to determine the variability of factors affecting the components of reliability (technical readiness).